CHRZEST SAKRAMENTEM WIARY W WYPOWIEDZIACH JANA PAWŁA II - Kulbacki, Piotr (Studia Pastoralne, 2023)
John Paul II often emphasized the role of baptismal spirituality. Some of his statements about baptism were referred to in the study. The Pope reminded us of the meaning of baptism as a covenant of faith. It is closely related to the conversion of man. Faith and conversion are personalistic, because they result from a personal decision of man recognizing Jesus Christ as his Savior and Lord and giving Him his life. Parents and godparents directly influence the upbringing of children and play an important role in the process of forming the life of faith. Evangelization is carried out in the name of the Churc‑h, therefore it is directed towards baptism that includes the Church community. Infused with the spirit of the gospel culture becomes an important means of evangelization. Baptism creates a common sacramental plane for all Christ’s followers. It has ecumenical consequences not only in relations between the Churches, but also within many families.